2011
DOI: 10.1002/jcp.22724
|View full text |Cite
|
Sign up to set email alerts
|

Malignant mesothelioma: Facts, Myths, and Hypotheses

Abstract: Malignant mesothelioma (MM) is a neoplasm arising from mesothelial cells lining the pleural, peritoneal, and pericardial cavities. Over 20 million people in the US are at risk of developing MM due to asbestos exposure. MM mortality rates are estimated to increase by 5-10% per year in most industrialized countries until about 2020. The incidence of MM in men has continued to rise during the past 50 years, while the incidence in women appears largely unchanged. It is estimated that about 50-80% of pleural MM in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
380
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 324 publications
(394 citation statements)
references
References 152 publications
1
380
0
7
Order By: Relevance
“…Mesothelial cells are the last remnant of mesoderm, so they are quite undifferentiated cells and maintain the ability to differentiate into different cell lines. Accordingly, some mesotheliomas have an epithelial morphology, others have a spindle cell morphology (often called sarcomatoid or fibrous mesothelioma) and others show a mixture of the two morphologies (called biphasic mesotheliomas) (1). More rare variants exist, but they are mostly a curiosity for the pathologist and have little clinical significance except that they are often misdiagnosed because they are rare and pathologists are not familiar with them.…”
Section: Pathologymentioning
confidence: 99%
See 2 more Smart Citations
“…Mesothelial cells are the last remnant of mesoderm, so they are quite undifferentiated cells and maintain the ability to differentiate into different cell lines. Accordingly, some mesotheliomas have an epithelial morphology, others have a spindle cell morphology (often called sarcomatoid or fibrous mesothelioma) and others show a mixture of the two morphologies (called biphasic mesotheliomas) (1). More rare variants exist, but they are mostly a curiosity for the pathologist and have little clinical significance except that they are often misdiagnosed because they are rare and pathologists are not familiar with them.…”
Section: Pathologymentioning
confidence: 99%
“…More rare variants exist, but they are mostly a curiosity for the pathologist and have little clinical significance except that they are often misdiagnosed because they are rare and pathologists are not familiar with them. Histologically, the epithelial variants are less aggressive than the spindle cell variants (1). Biphasic malignancies tend to behave according to the prevalent histological composition: the more fibrous they are, the more malignant they are (1).…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…The average latency of 40-45 years or more since the start of the exposure as found in studies with adequately long follow-up time explains the pattern of the observed mesothelioma incidence increases over the last decades with an estimated 43,000 annual deaths worldwide and why substantial decreases are not expected before 2020 [2]. Time trends indicate a slow shift of disease burden to countries consuming asbestos most recently [3], while incidence has peaked in most western industrialized countries after the ban of asbestos import and use in the eighties and nineties of last century [4]. Other possible causes are ionizing radiation, endemic erionite exposure and chronic inflammation of the pleura [3].…”
Section: Introductionmentioning
confidence: 85%
“…The median survival time commonly does not exceed 12–18 months after diagnosis 1. Therefore, biomarkers for early detection are imperative even for experienced pathologists.…”
mentioning
confidence: 99%